Unraveling the Sociolinguistic Dynamics of Adolescent Slang Usage in Palu City's WhatsApp Social Media - Suparni, Suparni; Mardiah, Mardiah; Putra, Muhammad Ryan (Yayasan Kyadiren, 2022)
This study examines the usage of slang in WhatsApp social media by teenagers in Palu, Indonesia, and aims to identify the forms of slang usage and the factors influencing Palu teenagers to use slang in their daily conversations on social media. By conducting observations and interviews, the study found unique uses of regional slang in social media. Teenagers tend to use inaccurate language that deviates from the rules of Indonesian language and mix Indonesian language with foreign languages, such asEnglish, leading to disorganized language use. The development of digitalization has contributed to the emergence of new languages. Cultural and regional backgrounds are also influential factors that cause the shift towards using Bahasa Indonesia. This qualitative research provides insights into how the use of slang in social media affects language use among teenagers in Palu.